2007
DOI: 10.1007/s11010-007-9429-2
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Fe-Aox29, a novel antioxidant derived from a molecular combination of Idebenone and vitamin E, in immortalized fibroblasts and fibroblasts from patients with Friedreich Ataxia

Abstract: Friedreich Ataxia (FRDA), the most frequent inherited ataxia, is not only characterized by progressive gait and limb ataxia, but in most cases is also accompanied by a severe hypertrophic cardiomyopathy. This life threatening symptom can be ameliorated by the administration of idebenone, a short chain quinone antioxidant, supporting additional evidence that oxidative stress plays a major role in the pathogenesis of this disease. In this study we analyze the combinatorial effect of different antioxidants on cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 35 publications
0
19
1
Order By: Relevance
“…Moreover, other studies have found increased plasma and urinary levels of oxidative stress markers in FRDA patients [13][14][15][16][17] and have demonstrated that some antioxidants, such as idebenone and vitamin E, might have a protective role [18,19].…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, other studies have found increased plasma and urinary levels of oxidative stress markers in FRDA patients [13][14][15][16][17] and have demonstrated that some antioxidants, such as idebenone and vitamin E, might have a protective role [18,19].…”
Section: Introductionmentioning
confidence: 98%
“…34,35 The cells were subjected to L-buthionine (S,R)-sulfoximine (BSO), an inhibitor of de novo glutathione (GSH) biosynthesis. 36 The half-maximal effective concentrations (EC 50 ) were determined (Table 1).…”
mentioning
confidence: 99%
“…Oxidative damage-induced death of FRDA fibroblasts was blocked by exogenous antioxidants. 34,35 Compound 6, 7, and 9 were by far the most efficient, having EC 50 values of 22 ± 7, 25 ± 4, and 32 ± 4 nM, respectively (Table 1). Again, in this assay the optimal side chain length was between 14 and 16 atoms.…”
mentioning
confidence: 99%
“…Notably, the antioxidant effect of idebenone in several studies was enhanced in presence of complex II substrates [25,26], suggesting that the antioxidant effect of idebenone is dependent on the reduced form of the molecule, a hypothesis that was later experimentally confirmed [27]. In line with its antioxidative activity, idebenone increased viability of glutathione (GSH)-depleted cells [28][29][30][31]. Moreover, in an ex vivo model of staurosporin-stressed retinal neurons, idebenone normalized mitochondrial and cytoplasmic ROS levels in these cells and prevented the associated cell death [32].…”
Section: Pharmacodynamicsmentioning
confidence: 89%